Launching deep subwavelength bulk plasmon polaritons through hyperbolic metamaterials for surface imaging with a tuneable ultra-short illumination depth. Issue 38 (21st September 2016) - Kong, Weijie; Du, Wenjuan; Liu, Kaipeng; Wang, Changtao; Liu, Ling; Zhao, Zeyu; Luo, Xiangang
Abstract : Hyperbolic metamaterial could produce uniform, large area surface imaging illumination sources with skin depth even beyond 10 nm. Abstract : Hyperbolic metamaterials (HMMs) composed of multiple nanometal–dielectric films are proposed for launching deep subwavelength bulk plasmon polaritons (BPPs) as uniform, large area surface imaging illumination sources with a skin depth even beyond 10 nm. Benefiting from the coupled plasmon modes over a wide wavevector range in HMMs, the illumination depth could be continually tuned, simply by adjusting the incidence angle of light impinged on a grating structure for BPP excitation. As an example, the illumination depths of 19–63 nm at a light wavelength of 532 nm are demonstrated with SiO2 –Ag multifilms. Moreover, the structure holds its deep subwavelength illumination depth for a broad light wavelength range, resembling that of light total internal reflection in a prism with an ultra high refractive index. Furthermore, a fluorescent nanoparticle based micro-zone system was employed for estimating the illumination depth of the HMM structure. The method is believed to provide access for surface imaging features in ultra thin layers especially for bio-samples.